A PERSONAL HISTORY OF THE OPHIOLITE CONCEPT - Moores E.M. (My University, 2003)
Since their original recognition in the early nineteenth century, ophiolites have been an integral feature of European Alpine-Mediterranean tectonic ideas. Ophiolites were not widely accepted by English-writing geologists until the late 1960s. Prior to that time, discussions in the English-language literature centered on the nature of the peridotites and volcanic rocks as separate entities. The development of the ophiolite concept went hand-in-hand with development of ideas of plate tectonics. As with plate tectonics, ophiolites are in a post-revolutionary, "mopping up" phase of scientific development. My personal experience in ophiolites began in the early 1960s in Greece, and has extended to the Troodos complex, Cyprus, western North America, and other localities. I recount my personal experiences with working on ophiolites during development of the plate tectonic revolution and its aftermath.